Sugarcane Variety Census: Florida 2004 - B. Glaz; J. Vonderwell; Robert A. Gilbert (EDIS)
This document is SS AGR 267, part of the Florida Sugarcane Handbook, published by the UF Agronomy Department, June - October 2007.